A Rare Complication of Herpes Zoster: Segmental Zoster Paresis - Teo, Hooi Khee (Case Rep Med, 2016)
Herpes zoster is a common presentation in both the community and emergency department; however segmental zoster paresis is a rare complication that can lead to misdiagnosis. We present a case of a 74-year-old Indian gentleman with a background of well controlled diabetes mellitus, hypertension, and ischaemic heart disease who presented with sudden right lower limb weakness. This was preceded by a 5-day history of paraesthesia starting in the right foot and ascending up the right lower limb. On examination, there was a characteristic vesicular rash in the L2/3 region with MRC grading 3/5 in the right hip flexors. The rest of the neurological examination was unremarkable. MRI of the spine did not show any evidence of spinal disease. The patient was initiated on IV acyclovir with improvement of the lower limb weakness to MRC grading 5/5 as the vesicles improved. This is an interesting case as it highlights a rare presentation of zoster: segmental motor paresis that recovered fully with resolution of the rash. It shows the importance of recognizing motor neuropathy as a complication of shingles as it has a very good prognosis with most patients regaining full motor function of the affected limb with treatment.